OP0232 C1qtnf4 Mutation Identified by Exome Sequencing Is Associated with Systemic Lupus Erythematosus and Dysregulation of Tnf-Induced Apoptosis. (15th July 2016) - Mauro, D.; Lewis, M.J.; Pullabhatla, V.; Vyse, S.; Simpson, M.; Cunninghame-Graham, D.; Syvanen, A.C.; Pitzalis, C.; de Rinaldis, E.; Vyse, T.J.
Abstract : Background: Whole exome sequencing of DNA samples from 30 UK SLE trios identified a de novo nonsynonymous mutation in C1QTNF4 gene associated with juvenile onset, severe SLE. C1QTNF4 encodes the secretory protein C1q/TNF-related protein 4, a member of the C1q family, characterized by two highly conserved C1q domains with structural similarity to adiponectin. C1QTNF4 has been implicated in NF-κB signalling and regulation of energy metabolism. Objectives: To characterize the structural and functional consequences of the C1QTNF4 C594G mutation (p.His198Gln) on TNF signalling and NF-κB activation. Methods: Whole exome sequencing of 90 individuals from 30 UK SLE trios was analysed to identify a list of de novo mutations associated with SLE. Resulting mutations were then filtered by likelihood of being deleterious and confirmed by Sanger sequencing of affected families. In silico modelling of wild type C1QTNF4 and C1QTNF4 p.His198Gln protein conformation was performed using Phyre2 and Pymol. The C1QTNF4 p.His198Gln mutation was reproduced in vitro by site-directed mutagenesis of pCMV6-C1QTNF4 vector, confirmed by Sanger sequencing. Secreted supernatants of C1QTNF4 and mutant C1QTNF4 p.His198Gln expressed in HEK293 cells were analysed for effects on secretion and oligomerization by chromatography and western blot. The effect of C1QTNF4 p.His198Gln on TNF-induced NF-κB activation was assessed in HEK293-NF-κB reporter cell line. The effect of the mutation on TNF-induced apoptosis was studied in L929 cells by luminescent cell titre assay. Results: The G594C mutation in C1QTNF4 results in a histidine to glutamine substitution at position 198 within the second globular C1q domain, resulting in significant change to the conformation of the second domain according to computational 3D modelling. The p.His198Gln mutation had no effect on protein secretion or oligomerization comparing C1QTNF4 and mutant C1QTNF4 p.His198Gln. Functional experiments revealed an inhibitory effect of secreted C1QTNF4 p.His198Gln on TNF signalling. Although wild type C1QTNF4 had no effect on TNF-stimulated activation of NF-kB and TNF-induced cell death, secreted C1QTNF4 p.His198Gln demonstrated significant inhibition of TNF-stimulated activation of NF-κB (p<0.01) and inhibition of TNF-induced apoptosis in L929 cells (p<0.0001). Conclusions: Using exome sequencing, we have identified a novel de novo mutation G594C (p.His198Gln) in C1QTNF4 associated with development of SLE, which results in a gain-of-function change in conformation of the second C1q domain of C1QTNF4. Secreted C1QTNF4 p.His198Gln inhibited both TNF mediated activation of NF-kB and TNF-induced apoptosis. Thus the association of C1QTNF4 G594C with SLE is consistent with the known role of dysregulated apoptosis in SLE pathogenesis, and the association of TNF blockade with development of SLE-type autoimmunity. Disclosure of Interest: None declared